An orthogonal photoresponsive tristable [3]rotaxane with non-destructive readout. Issue 7 (3rd February 2021) - Li, Wan-Xia; Yin, Yong-Fei; Duan, Hong-Ying; Liu, Li-Juan; Kong, Li-Chun; Zhan, Tian-Guang; Zhang, Kang-Da
Abstract : An orthogonal photoresponsive [3]rotaxane is constructed by introducing two orthogonal photoswitchable azobenzene binding sites, and it features reversible photoregulated tristate absorption spectral changes with non-destructive readout capability. Abstract : In this paper, a unique orthogonal photoresponsive tristable [3]rotaxane molecular shuttle (R1 ) is constructed, which consists of two CBPQT 4+ macrocycles interlocked via a dumbbell component containing three recognition sites, including photoswitchable azobenzene (AB) and naphthalene-derived azobenzene (NP-AB) units separated by a 1, 5-dioxynaphthalene (DNP) unit. The two azo units that are encapsulated by the CBPQT 4+ macrocycles in the pristine state can be E / Z photoisomerized separately upon irradiation using UV (365 nm) and yellow (>550 nm) light (for the AB unit) and using blue (420–430 nm) and yellow (>550 nm) light (for the NP-AB unit), thus achieving the distinctive orthogonal phototriggered shuttling of the CBPQT 4+ macrocycles between the azo and DNP units. This means that charge transfer (CT) absorption (at 620 nm, generated from the NP⊂CBPQT 4+ encapsulation complex) related to R1 can be fully photoregulated between three spectral states with good reversibility. Moreover, UV-light-irradiated [2]rotaxane analogues that are embedded with NP-AB or AB units are found to be insensitive to red light (620 nm) irradiation. These features, together with the peculiarity of the orthogonal photo-responsiveness, enable this novel photochromic [3]rotaxane to be potentially applied as a multistate molecular switch or as an optical information storage medium with non-destructive readout.